Vascular occlusion of the facial transverse artery after hyaluronic acid filler injection. A case report and 8-step protocol for treatment of acute vascular complications - Denkova, Radina; Georgieva, Iliana; Kantardjiev, Vessel (Aesthetic Medicine, 2024)
Nowadays, dermal fillers are increasingly used for facial rejuvenation and soft tissue augmentation to counteract skin ageing. Even with good anatomical knowledge of the injectors, complications are being observed after the application of volume enhancer products. This study aims to report a case of acute vascular occlusion after hyaluronic filler injections in the sub-malar area of the face. A short overview of possible side effects and a simple treatment protocol are also presented.